Distribution of surficial sediments in the ocean around New Zealand/Aotearoa. Part B: continental shelf. Issue 1 (2nd January 2019) - Bostock, Helen; Jenkins, Chris; Mackay, Kevin; Carter, Lionel; Nodder, Scott; Orpin, Alan; Pallentin, Arne; Wysoczanski, Richard
ABSTRACT: This paper provides new maps of the surficial sediment distribution on the continental shelf (0∼150 m water depth) of New Zealand based on a new database – nzSEABED. The maps of percent mud, sand, gravel and carbonate, are compared with previous research to provide a comprehensive update of the surficial sediment distributions on the continental shelf, together with a review of the main environmental (oceanographic and climatic), geomorphological and geological processes and human activities that have influenced sediment deposition. Continental shelves are dynamic regions that are in a constant state of flux from floods, storms, tides, waves, earthquakes and volcanic activity. While some of these events may be captured by individual samples, the compilation of >23, 000 samples collected and analysed over 60 years provides a long-term average distribution of sediments on the continental shelf that can inform future research and coastal management.